The young people's Wesley - McDonald, W. (Eaton & Mains, 1901)
Born in troublous times -- The Wesley family -- Wesley's early life -- Epworth rappings -- Origin of the Holy Club -- Wesley in America -- Wesley's religious experience -- Wesley's multiplied labors -- Wesley's domestic relations -- Wesley's persecutions -- Wesley and his theology -- Wesley as a man -- Wesley as a preacher -- Wesley as a reformer -- Wesley and American Methodism prior to 1766 -- Wesley and American Methodism -- Wesley approaching the close of life -- Wesley and his triumphant death -- Wesley's character as estimated by unbiased judges -- The greater Wesley of the opening century.